Types of Rural Extensionists’ Expectations of Psychology and Their Implications on Psychologists’ Practice - Landini, Fernando Pablo (2016)
Psychology has great potential for contributing to rural development, particularly through supporting rural extension (RE). In this paper, the types of expectations extensionists have of psychology are identified, as well as possible ways of integrating psychosocial knowledge into the RE context. Rural extensionists from 12 Latin American countries were surveyed (n = 654). Of them, 89.4 % considered psychology could contribute to rural extension and commented on how this would be possible. Expectations were categorised and the nine mentioned by more than 20 % of them were utilized to conduct a two-steps cluster analysis. Three types of extensionists’ expectations were identified: one wherein working with extensionists was highlighted; another characterised by a focus on working with farmers; and a third featuring a traditional, diffusionist extension approach, which views farmers as objects of psychologists’ interventions. With the first type, psychologists should not neglect working with farmers and with the second, with extensionists. With the third type, reflecting on the expectations themselves and their underlying assumptions seems essential.